(untitled) - Bozeman, Barry (New York, NY, 1983)
Investigates U.S. manufacturing companies' different sources of technological knowledge--from internal research and development to the importation or buying of knowledge.
Keywords: Đổi mới công nghệ,Technological innovations; Hoa Kỳ,United States